2024
DOI: 10.3758/s13415-024-01166-z
|View full text |Cite
|
Sign up to set email alerts
|

A negative emotional state impairs individuals’ ability to filter distractors from working memory: an ERP study

Chaoxiong Ye,
Ruyi Liu,
Lijing Guo
et al.

Abstract: Capacity-limited visual working memory (VWM) requires that individuals have sufficient memory space and the ability to filter distractors. Negative emotional states are known to impact VWM storage, yet their influence on distractor filtering within VWM remains underexplored. We conducted direct neural measurement of participants (n = 56) who conducted a lateralized change detection task with distractors, while manipulating the emotional state by presenting neutral or negative images before each trial. We found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 56 publications
(109 reference statements)
0
0
0
Order By: Relevance
“…Previous studies have shown that N2pc can be observed 170-220 ms after retro-cue onset, and CDA can be observed 300 ms after retro-cue onset, persisting throughout maintenance 55,56,61,62,[72][73][74] . Accordingly, our time window of interest for N2pc was between 170 ms and 220 ms after retro-cue onset, and for CDA, it was between 300 ms and 1600 ms after retro-cue onset.…”
Section: Analysis Of N2pc and Cda Amplitudesmentioning
confidence: 92%
“…Previous studies have shown that N2pc can be observed 170-220 ms after retro-cue onset, and CDA can be observed 300 ms after retro-cue onset, persisting throughout maintenance 55,56,61,62,[72][73][74] . Accordingly, our time window of interest for N2pc was between 170 ms and 220 ms after retro-cue onset, and for CDA, it was between 300 ms and 1600 ms after retro-cue onset.…”
Section: Analysis Of N2pc and Cda Amplitudesmentioning
confidence: 92%